Promoting physical activity and youth development in schools: the case for near-peer coaches - St. Pierre, Christine; Mitchell, Jerita; Guan, Win; Sacheck, Jennifer M. (Frontiers in Public Health, 2024)
Background: Sports-based youth development (SBYD) programs provide an inclusive, supportive environment for promoting physical activity as well as nurturing the development of life skills which, in combination, promote physical, mental, and emotional health in youth. The Up2Us Sports SBYD program was implemented in six schools in New Orleans, Louisiana in 2020-2022, where near-peer coaches from the community were placed in schools and present throughout the school day. The intervention period straddled the COVID-19 pandemic as well as extreme weather events, modifying program delivery.Process/methods: An exploratory case study was conducted to understand participant experience amid program disruptions and modifications, as well as their perceptions of program impact on physical activity and health. Interviews with coaches (n=7), focus groups with youth (n=14) and program observation data were triangulated to provide a description of the case.The major theme that emerged from the case study was the centrality of the near-peer mentorship relationships between coaches and youth. Participants believed near-peer relationships facilitated life skill development and increased opportunity for physical activity in schools, but pressures on coaches' time and external challenges in the community were limiting factors to the extent of program impact.This community case study demonstrates the potential role for near-peer mentors in influencing the health and well-being of youth from under-resourced communities and highlights the opportunity for school-based SBYD programming to provide youth with a consistent source of both relational and physical activity support.